Factors Influencing Antenatal Care Examinations For Pregnant Women In The Working Area - Pardede, Sarah Yosephine; Raja , Sarma Lumban; Sibero , Jitasari Tarigan; Suroyo , Razia Begum; Fitria , Aida (Jurnal Perilaku Kesehatan Terpadu, 2023)
Antenatal care examinations based on integrated antenatal care services are 6 visits during pregnancy. Early detection in pregnancy determines the presence of anemia in pregnancy which can cause bleeding during delivery, signs of complications from early delivery such as pelvic deformities, multiple pregnancies and complications during pregnancy such as pre-eclampsia, chronic diseases such as heart and lung disease and genetic diseases such as diabetes, hypertension. , or congenital defects and also infectious diseases such as HIV and hepatitis. The method in this research is a Mixed Method using a Cross Sectional approach. The population in this study was 288 pregnant women and a sample of 74 pregnant women in the working area of ??the Patumbak Health Center, Deli Serdang Regency. The analysis used includes univariate, bivariate and multivariate analysis with multiple logistic regression. The results of this study indicate that there are factors that influence maternal antenatal care examinations, namely knowledge (p=0.042), attitude (p=0.017), occupation (p=0.725), age (p=0.0257), parity (p=0.196 ), source of information (p=0.278), husband's support (p=0.031), and service accessibility (p=0.001). The conclusion in this study is that there is an influence between maternal knowledge, attitudes, husband's support, and service accessibility with antenatal care examinations. Meanwhile, occupation, age, parity and source of information had no influence on antenatal care examinations.